Industry 4.0 and Lean Manufacturing Practices: An Approach to Enhance Operational Performance in Singapore’s Manufacturing Sector - Lee, Kin Seng; Mohd Nor, Norasmiha; Ismail, Fadillah (Research in Management of Technology and Business, 2021)
Lean Manufacturing Practices (LMP) is a technique to reduce waste and enhance operational performance. On the other hand, the adoption of Industry Relation (IR 4.0) is known as a strategy to provide a greater capability for lean manufacturing practices to enhance the efficiency of the manufacturing line performance and satisfy consumer requirements. The main objective is to examine the integration of lean and IR 4.0 to enhance operational performance. This study was conducted using the survey method. Through this research, a total sample size of 51 validated companies’ respondents participated in this research. Multiple regression was the main analysis in this research. The finding of this research showed that the operational performance was in a high and moderate level and there was a positive relationship between the Top Management Leadership (r = 0.540), Employees Training (r = 0.582), Customer Involvement (r = 0.528), Continuous Improvement (r = 0.783), Supplier Partnership (r = 0.542), and Small Group Problem Solving (r = 0.530) as well as Industry Relation 4.0 (r = 0.391). This study also proved that the Lean Manufacturing Practice (LMP) and Industry Relation (IR 4.0) had a significant impact on the operational performance of R-square = 0.644. This research can beneficially contribute to future research in understanding the significance of the IR 4.0 and LMP approaches to improve the manufacturing industry’s operational performances.